2011
DOI: 10.1111/j.1600-0889.2011.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Particle chemical properties in the vertical column based on aircraft observations in the vicinity of Cape Verde Islands

Abstract: A B S T R A C T During the second Saharan Mineral Dust Experiment (SAMUM-2) field campaign, particles with geometric diameters (d) between ∼0.1 and 25 μm were collected on board of the Deutsches Zentrum für Luft-und Raumfahrt (German Aerospace Center, DLR) Falcon aircraft. Size, chemical composition and mixing state of aerosols sampled (spatially and vertically resolved) along the West African coastline and in the Cape Verde Islands region were determined by electron microscopy. A pronounced layer structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 37 publications
(64 reference statements)
9
70
1
Order By: Relevance
“…J.S. Reid et al, 2003;Coz et al, 2009;Okada et al, 1987;Li and Osada, 2007) from short-range transported dust (including Kandler et al, 2007;Kandler et al, 2009;Kandler et al, 2011;Lieke et al, 2011;Scheuvens et al, 2011;Wagner et al, 2012;Jeong et al, 2016;Okada et al, 2001 -Hohhot) based on the attributions in publications that reported these measurements. Note that there is not enough data to assess changes of HWR during transport (see Figure S4).…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…J.S. Reid et al, 2003;Coz et al, 2009;Okada et al, 1987;Li and Osada, 2007) from short-range transported dust (including Kandler et al, 2007;Kandler et al, 2009;Kandler et al, 2011;Lieke et al, 2011;Scheuvens et al, 2011;Wagner et al, 2012;Jeong et al, 2016;Okada et al, 2001 -Hohhot) based on the attributions in publications that reported these measurements. Note that there is not enough data to assess changes of HWR during transport (see Figure S4).…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Several lidars (Groß et al, 2011a; Tesche et al, 2011a), Sun photometers (Toledano et al, 2011), and a station for extensive particle sampling and in‐situ aerosol characterization (Kandler et al, 2011; Müller et al, 2011; Schladitz et al, 2011) were deployed at Praia airport together with the Falcon research aircraft of the German Aerospace Centre (DLR). The latter was applied for in situ particle sampling (Lieke et al, 2011; Petzold et al, 2011) and equipped with a high spectral resolution lidar (HSRL, Esselborn et al, 2009) for vertical profiling. Additional in situ measurements at ground level give information about aerosol concentrations, size distributions, as well as the hygroscopicity and refractive index of the sampled particles.…”
Section: Datamentioning
confidence: 99%
“…Denjean et al (2015) performed detailed chemical analysis of long-range transported dust with diameters > 1 µm in Puerto Rico (in situ observations at ground level) in the summer of 2012 and found that about 10 % of the dust particles were internally mixed and showed sulfate and chloride coatings during a strong dust event, and 3-6 % of the dust particles showed an internal mixture with sea salt particles. Lieke et al (2011) (airborne observations) and Kandler et al (2011) (ground-based observations) found during the SAMUM-2 campaign (Cabo Verde, January-February 2008, biomass burning season in central-western Africa) internal silicate-sulfate mixtures in roughly 10-20 % of the analyzed particles in the 500-1000 nm range and about 10 % for particles with diameters > 1 µm. An internal mixture of dust and soot was not observed in the free tropospheric layers .…”
Section: Polly Xtmentioning
confidence: 99%